Altered modulation of lamin A/C‐HDAC2 interaction and p21 expression during oxidative stress response in HGPS. Issue 5 (15th August 2018) - Mattioli, Elisabetta; Andrenacci, Davide; Garofalo, Cecilia; Prencipe, Sabino; Scotlandi, Katia; Remondini, Daniel; Gentilini, Davide; Di Blasio, Anna Maria; Valente, Sergio; Scarano, Emanuela; Cicchilitti, Lucia; Piaggio, Giulia; et al.
Abstract: Defects in stress response are main determinants of cellular senescence and organism aging. In fibroblasts from patients affected by Hutchinson–Gilford progeria, a severe LMNA ‐linked syndrome associated with bone resorption, cardiovascular disorders, and premature aging, we found altered modulation of CDKN1A, encoding p21, upon oxidative stress induction, and accumulation of senescence markers during stress recovery. In this context, we unraveled a dynamic interaction of lamin A/C with HDAC2, an histone deacetylase that regulates CDKN1A expression. In control skin fibroblasts, lamin A/C is part of a protein complex including HDAC2 and its histone substrates; protein interaction is reduced at the onset of DNA damage response and recovered after completion of DNA repair. This interplay parallels modulation of p21 expression and global histone acetylation, and it is disrupted by LMNA mutations leading to progeroid phenotypes. In fact, HGPS cells show impaired lamin A/C‐HDAC2 interplay and accumulation of p21 upon stress recovery. Collectively, these results link altered physical interaction between lamin A/C and HDAC2 to cellular and organism aging. The lamin A/C‐HDAC2 complex may be a novel therapeutic target to slow down progression of progeria symptoms.